2020
DOI: 10.1177/1039856220928867
|View full text |Cite
|
Sign up to set email alerts
|

New Zealand community mental healthcare provider experience in schizophrenia management with 3-monthly paliperidone palmitate

Abstract: Objectives: To understand the impact of 3-monthly treatment with paliperidone palmitate on patient management, including non-adherence and relapse, from a psychiatrist and nurse perspective for 73 patients enrolled in a patient familiarisation programme (PFP) in New Zealand. Methods: An online questionnaire was sent to clinicians with at least 6 months of regular interaction with PFP patients. Questions addressed treatment effectiveness and patient management changes. Analyses are descriptive only and do not r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Treatment with PP3M has been associated with symptomatic remission and stability, 7,8 prevention of relapse 9 and important downstream benefits of enabling a shift in focus from medication-related issues towards health, well-being and recovery goals. 1,8…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment with PP3M has been associated with symptomatic remission and stability, 7,8 prevention of relapse 9 and important downstream benefits of enabling a shift in focus from medication-related issues towards health, well-being and recovery goals. 1,8…”
Section: Discussionmentioning
confidence: 99%
“…Long-acting injectable preparations of antipsychotic medications can support treatment persistence and adherence in patients with schizophrenia, prevent hospitalisation or relapse and improve social functioning. 1,2 Compared to first-generation medications and second-generation oral medications, second-generation antipsychotic long-acting injectable (SGA LAI) therapies are associated with longer treatment persistence, 3 with additional advantages including fewer extrapyramidal side effects, 4 reduced risk of overdose; predictable serum concentrations; and differentiation between lack of efficacy and lack of adherence. 5 Despite these advantages, a recent cohort study reported that older long-acting therapies were still used by 20% of patients.…”
mentioning
confidence: 99%
“…A study of Cassidy and Miles (2020) evaluated by an online-questionnaire the impact of PP3M on patient management, including non-adherence and relapse, from a psychiatrist (n=7) and nurse (n=17) perspective. 16 Treatment goals were met or exceeded, and psychiatrists were satisfied with treatment efficacy and relapse prevention. They concluded that from a clinician’s perspective, PP3M offers patients the potential to remain adherent and improve social functioning.…”
Section: Introductionmentioning
confidence: 99%